2021
DOI: 10.3389/fvets.2021.623666
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Abortions Revisited—Enhancing Abortion Diagnostics by 16S rDNA Amplicon Sequencing and Fluorescence in situ Hybridization

Abstract: Abortion in cattle causes significant economic losses for cattle farmers worldwide. The diversity of abortifacients makes abortion diagnostics a complex and challenging discipline that additionally is restrained by time and economy. Microbial culture has traditionally been an important method for the identification of bacterial and mycotic abortifacients. However, it comes with the inherent bias of favoring the easy-to-culture species, e.g., those that do not require cell culture, pre-enrichment, a variety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…However, many of the similar types of bacteria as identified in this study are reported to cause of abortions, as Salmonella enterica serovars including S. Dublin in cattle [23][24][25], Aeromonas species in equids [26] and bovines [27], Enterobacter agglomerans in equids [28,29], Moelerella wisconsensis in bovines [30,31], Xenorhabdus bovienii and X. poinarii in bovines [30], K. pneumoniae in cattle [27]. However, K. varians identified as cause of abortion and or me- [11,12,27,30,31,34,35] but some like K. varians and V. alginolyticus have rarely been associated with bovine infections but reported in human as opportunistic pathogens. Similar types of bacteria have been reported in vaginal tract of apparently healthy sows [35] and a closely related animal, mithun (Bos frontalis), to buffaloes [34] indicating that the bacteria identified in the present study might be opportunistic pathogens of reproductive tract.…”
Section: Discussionmentioning
confidence: 80%
“…However, many of the similar types of bacteria as identified in this study are reported to cause of abortions, as Salmonella enterica serovars including S. Dublin in cattle [23][24][25], Aeromonas species in equids [26] and bovines [27], Enterobacter agglomerans in equids [28,29], Moelerella wisconsensis in bovines [30,31], Xenorhabdus bovienii and X. poinarii in bovines [30], K. pneumoniae in cattle [27]. However, K. varians identified as cause of abortion and or me- [11,12,27,30,31,34,35] but some like K. varians and V. alginolyticus have rarely been associated with bovine infections but reported in human as opportunistic pathogens. Similar types of bacteria have been reported in vaginal tract of apparently healthy sows [35] and a closely related animal, mithun (Bos frontalis), to buffaloes [34] indicating that the bacteria identified in the present study might be opportunistic pathogens of reproductive tract.…”
Section: Discussionmentioning
confidence: 80%
“…A panel of commercial qPRC and RT-qPCR assays were used for a rapid diagnosis of these pathogens. These molecular methods have been reported to provide highly sensitive, specific and rapid tools for the specific detection of different abortifacient infectious agents in various clinical samples, with multi-screening qPCR approaches allowing the simultaneous detection of the main abortive agents [ 45 , 46 , 47 ]. It is generally accepted that both standard PCR and qPCR provides diagnostic information on pathogens existing in samples [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…genus, which infects humans, domestic and wild animals [ 1 ]. In bovines, leptospirosis plays an important role as one of the main reproductive diseases, leading to important economic hazards [ 2 , 3 ]. Leptospires can colonize the genital tract and kidneys of bovines and its transmission occurs from direct contact with infected animals or a contaminated environment [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since different pathogens can lead to abortions in cattle, the proper diagnosis is crucial to implement control measures. The necropsy of aborted fetuses followed by molecular analysis of its tissues and placenta is highly encouraged for the diagnosis of animal leptospirosis [ 3 , 22 , 23 ]. Detecting bacterial pathogens in fetuses is particularly challenging due to autolysis, which can happen even before the abortion is expelled, interfering with the bacterial load in the organs [ 12 , 13 , 23 ].…”
Section: Introductionmentioning
confidence: 99%